Skills, not just diplomas : strengthening education systems in Eastern Europe and Central Asia - Søndergaard, Lars (World Bank, 2011)
Future growth in the countries in Eastern Europe and Central Asia (ECA) will increasingly depend on innovation. And innovation requires skills. This makes it important, as countries plan for recovery, to undertake reforms to reduce the skills shortages that the previous growth episode exposed. Education systems have a very important role to play in creating the right skills. But education systems in the region fall short of the demands of their economies in two major ways. The first is that despite high levels of enrollment they do not produce enough graduates with the right skills. Students gr.